2021
DOI: 10.1155/2021/5185758
|View full text |Cite
|
Sign up to set email alerts
|

Variable Heights Influence Lower Extremity Biomechanics and Reactive Strength Index during Drop Jump: An Experimental Study of Male High Jumpers

Abstract: Introduction. This study finds the lower limbs’ reactive strength index and biomechanical parameters on variable heights. Objective. This research aims to reveal the effects of drop height on lower limbs’ reactive strength index and biomechanical parameters. Methods. Two AMTI force platforms and Vicon motion capture system were used to collect kinematic and dynamic signals of the lower limbs. Results. The drop height had significant effects on peak vertical ground reaction force and peak vertical ground reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…However, the short contact time requires that the low extremity need to resist the high loading impact in the higher drop height to keep the fast muscle contraction. It is precisely that high jump training contained numerous fast takeoffs and full flexion and extension with tremendous impact [ 10 ]; it makes the muscle tendon complex absorb the elastic energy in the eccentric phase and utilize them well in the concentric phase with the excessive height (0.75 m). McBride and Snyder found that higher bounce heights were produced in the training group of sprinters and jumpers who performed drop jumps at 40 cm, 60 cm, and 80 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the short contact time requires that the low extremity need to resist the high loading impact in the higher drop height to keep the fast muscle contraction. It is precisely that high jump training contained numerous fast takeoffs and full flexion and extension with tremendous impact [ 10 ]; it makes the muscle tendon complex absorb the elastic energy in the eccentric phase and utilize them well in the concentric phase with the excessive height (0.75 m). McBride and Snyder found that higher bounce heights were produced in the training group of sprinters and jumpers who performed drop jumps at 40 cm, 60 cm, and 80 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Byrne et al [ 5 ] revealed that 0.4 m and 0.6 m are an optimal loading height reactive strength index. Zehao et al [ 9 ] found that at a height of 0.45 m, high jumper's reactive strength index and average power output reached the peak [ 10 ]. Di Giminiani and Petricola [ 11 ] suggest that athletes need to determine their individual optimal loading height for average power output, in order to control their training process.…”
Section: Introductionmentioning
confidence: 99%
“…e regulation of reflex muscles such as muscle spindle will enhance the preactivation of muscle-tendon complex at the excited lower limbs, which is manifested as the higher stiffness of muscle-tendon complex and accumulation of more elastic potential energy [35]. When it exceeds the optimal loading height, due to the protection from upper spinal nerves, the muscle-tendon complex is protected from a high-load impact and the nerves are adapted to the strategy, the inhibition flow of muscle spindle will lower the preactivation of muscles [9], which is mainly manifested as lower stiffness of the muscle-tendon complex 43 , the significant extension of supporting duration and the loss of the stored elastic potential energy.…”
Section: Biomechanical Mechanism Of Optimalmentioning
confidence: 99%